Teori Dan Ilustrasi Syirkah Dalam Ekonomi Islam - Sarwo Edi (AGHNIYA : Jurnal Ekonomi Islam, 2020)
In matters of Islamic economics there are practically a lot of trade agreements. Franchising is a form of trade cooperation, in principle, may be done as long as there is no proof that forbids it, but it must be in line with sharia maqasid. In the process of the ongoing trade partnership, sometimes a dispute can occur, and the disagreement that eventually the partnership ended in a state of retreat, even not infrequently out of business. For this reason, it is time for the Islamic ummah to start their partnership system, referring to the Islamic model. Namely syirkah, so the system has a guarantee where the contract of choice is many and gives a definite direction and leads to peace of mind. At the very least, trade agreements using syirkah for business people are worth of worship, so that we are close to achieving the pleasure of Allah SWT.